Assessment of prehospital hemorrhage and airway care using a simulation model. Issue 1 (July 2018) - Skube, Mariya E.; Witthuhn, Seth; Mulier, Kristine; Boucher, Bonnie; Lusczek, Elizabeth; Beilman, Greg J.
Abstract : BACKGROUND: The quality of prehospital care impacts patient outcomes. Military efforts have focused on training revision and the creation of high-fidelity simulation models to address potentially survivable injuries. We sought to investigate the applicability of models emphasizing hemorrhage control and airway management to a civilian population. METHODS: Prehospital health care providers (PHPs) undergoing their annual training were enrolled. A trauma scenario was simulated with two modules: hemorrhage control and airway management. Experienced raters used a validated tool to assess performance. Pearson correlation, logistic regression, and χ 2 tests were used for analysis. RESULTS: Ninety-five PHPs participated with a mean experience of 15.9 ± 8.3 years, and 7.4% reported past military training. The PHPs' overall execution rate of the six hemorrhage control measures varied from 38.9% to 88.4%. The median blood loss was 1, 700 mL (interquartile range, 1, 043 – 2, 000), and the mean global rater score was 25.0 ± 7.4 (scale, 5–40). There was a significant relationship between PHP profession and past military experience to their consideration of blood transfusion and tranexamic acid. An inverse relationship between blood loss and global rater score was found ( r = −0.59, n = 88, p = 1.93 × 10 −9 ). After simulated direct laryngoscope failure in the airway module, 58% of PHPs selected video laryngoscopy over placement of a supraglottic airway. Eighty-six percent of participants achieved bilateral chest rise in the manikin regardless of management method. Participants reported improved comfort with skills after simulation. CONCLUSION: Our data reveal marginal performance in hemorrhage control regardless of the PHP's prior experience. The majority of PHPs were able to secure an advanced airway if direct laryngoscope was unavailable with a predisposition for video laryngoscopy over supraglottic airway. Our findings support the need for continued training for PHPs highlighting hemorrhage control maneuvers and increased familiarity with airway management options. Improved participant confidence posttraining gives credence to simulation training. LEVEL OF EVIDENCE: Prognostic/epidemiological study, level III.